The power of bridging decision scales: Model coupling for advanced climate policy analysis - Tatiana Filatova; Joos Akkerman; Francesco Bosello; Theodoros Chatzivasileiadis; Ignasi Cortés Arbués; Amineh Ghorbani; Olga Ivanova; Nina Knittel; Jan Kwakkel; Francesco Lamperti; Nicholas R. Magliocca; Giacomo Marangoni; et al. (Proceedings of the National Academy of Sciences, 2025)
Climate policy faces increasingly complex challenges that span multiple human decision scales in nature–society systems. Contemporary climate policy models, while valuable and increasingly versatile in handling spatial and temporal scales, struggle to capture interacting multiscale decisions on the socioeconomic side. This perspective draws attention to the power of coupling among different modeling families, taking integrated assessment models (IAM), computable general equilibrium models (CGE), and agent-based models (ABM) as examples. Recent computational advances, maturity of models, availability of data, and interdisciplinary expertise make model coupling an increasingly feasible, effective, and useful tool for climate policy analysis. We examine the unique contributions of each modeling approach, highlight synergies from uniting their strengths, and discuss alternatives to and conditions for coupling. In addressing methodological challenges, we present examples of effective coupling of IAM–ABM–CGE, emphasizing the importance of maintaining model integrity while enhancing policy relevance. By bridging human decision scales and leveraging complementary strengths, coupled models can provide nuanced insights into climate–economy interactions, ultimately supporting effective and equitable—not just efficient and optimal—climate policies.